Chronic continuous abdominal pain: evaluation of diagnostic features, iatrogenesis and drug treatments in a cohort of 103 patients. Issue 10 (4th April 2019) - Kilgallon, Eleesia; Vasant, Dipesh H.; Green, Darren; Shields, Philip L.; Hamdy, Shaheen; Lal, Simon; Paine, Peter
Summary: Background: Chronic continuous abdominal pain (CCAP) is characteristic of centrally mediated gastrointestinal pain disorders. It consumes significant healthcare resources yet is poorly understood, with minimal cohort‐specific data in the literature. Aims: To examine in a large cohort of CCAP patients, (a) diagnostic features, (b) iatrogenic impact of opioids and surgery, (c) drug treatment effects and tolerance. Methods: Consecutive tertiary CCAP referrals to a neurogastroenterology clinic (2009‐2016) were reviewed for Rome IV and neuropathic pain criteria. Medical, surgical and drug histories, interventions and outcomes were correlated with clinical diagnosis and associated opioid use. Results: Of 103 CCAP patients (mean age 40 ± 14, 85% female), 50% had physiological exacerbations precluding full Rome IV Centrally Mediated Abdominal Pain Syndrome criteria. However, there were no significant differences between patients who satisfied Rome IV criteria and those who did not. Overall, 81% had allodynia (a nonpainful stimulus evoking pain sensation). Opioid use was associated with allodynia ( P  = 0.003). Prior surgery was associated with further operations post CCAP onset ( P  < 0.001). Although 68% had undergone surgical interventions, surgery did not resolve pain in any patient and worsened pain in 35%. Whilst duloxetine was the most effective neuromodulator ( P  = 0.003), combination therapy was superior to monotherapy ( P  = 0.007). Conclusions: This is currently the largest cohort CCAP dataset that supports eliciting neuropathic features, including allodynia, for a positive clinical diagnosis, to guide treatment. Physiological exacerbation of CCAP may represent visceral allodynia, and need not preclude central origin. Use of centrally acting neuromodulators, and avoidance of detrimental opioids and surgical interventions appear to predict favourable outcomes.